Spectroscopic changes induced by sonication of porphyrin-carbon nanotube composites in chlorinated solvents - GIORDANI, SILVIA; BLAU, WERNER (My University, 2007)
We report the spectroscopic changes of tetraphenylporphyrin carbon nanotube composites in a variety of chlorinated solvents such as chloroform, dichloroethane and dichlorobenzene as a result of sonication. Detailed data analysis suggests that protonation of the porphyrin core nitrogen atoms occurs as a result of sonodegradation of the solvent molecules. Extreme care must be taken when working with carbon nanotube composite solutions in chlorinated solvents, as sonication is always employed to disperse the nanotubes. When working with molecules that are capable of acting as a base someamount of protonation is inevitable and this may dramatically change the physicochemical properties of the composite materials.
PUBLISHED
Keywords: Physics; Chemistry